The roles of circular RNAs in nerve injury and repair - Zong, Ying; Dai, Yuqi; Yan, Junjie; Yu, Bin; Wang, Dong; Mao, Susu (Frontiers in Molecular Neuroscience, 2024)
Nerve injuries significantly impact the quality of life for patients, with severe cases posing life-threatening risks. A comprehensive understanding of the pathophysiological mechanisms underlying nerve injury is crucial to the development of effective strategies to promote nerve regeneration. Circular RNAs (circRNAs), a recently characterized class of RNAs distinguished by their covalently closed-loop structures, have been shown to play an important role in various biological processes. Numerous studies have highlighted the pivotal role of circRNAs in nerve regeneration, identifying them as potential therapeutic targets. This review aims to succinctly outline the latest advances in the role of circRNAs related to nerve injury repair and the underlying mechanisms, including peripheral nerve injury, traumatic brain injury, spinal cord injury, and neuropathic pain. Finally, we discuss the potential applications of circRNAs in drug development and consider the potential directions for future research in this field to provide insights into circRNAs in nerve injury repair.